A LINGUISTIC ANALYSIS OF VERBS EXPRESSING HUMAN BEHAVIOR IN ARABIC - Atul B (International Journal of Literature and Language Studies, 2023)
the Arabic language possesses a highly intricate morphological system that encodes complex semantic nuances directly into the lexical architecture of its verbs. This article provides a comprehensive linguistic analysis of verbs expressing human behavior in Arabic, focusing on the intersection of morphology (ṣarf), lexical semantics (dalāla), and cognitive linguistics. By examining the derivational patterns (awzān) of the Arabic root-and-pattern system, specifically Forms II through X, this study demonstrates how intentionality, reciprocity, pretense, and psychological states are grammatically codified. Furthermore, the article explores the cognitive metaphors underlying behavioral lexicon, revealing how spatial and physical concepts map onto social and moral conduct. The findings illustrate that Arabic behavioral verbs do not merely describe actions but provide a microscopic view into the social pragmatics and psychological dimensions of the human actor.